2014
DOI: 10.2147/dddt.s62176
|View full text |Cite
|
Sign up to set email alerts
|

Novel nanocrystal formulation of megestrol acetate has improved bioavailability compared with the conventional micronized formulation in the fasting state

Abstract: BackgroundMegestrol acetate is an effective treatment for improving appetite and increasing body weight in patients with cancer-associated anorexia. However, Megace® oral suspension (OS), a micronized formulation of megestrol acetate, has low bioavailability in the fasting state. To overcome this limitation, a nanocrystal formulation has been developed. This study was performed to evaluate the pharmacokinetics and tolerability of the nanocrystal formulation and to compare them with those of Megace® OS in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…In the simulation, the dosing scheme chosen was multiple dosing for 7 days assuming a steady-state, based on the drug elimination half-life of 20-50 hr reported in the literature [6][7][8]. The optimal daily dose, D*, to be administered under fasting conditions, was defined as the dose that minimizes the absolute relative error (ERR, %), which is defined as follows:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the simulation, the dosing scheme chosen was multiple dosing for 7 days assuming a steady-state, based on the drug elimination half-life of 20-50 hr reported in the literature [6][7][8]. The optimal daily dose, D*, to be administered under fasting conditions, was defined as the dose that minimizes the absolute relative error (ERR, %), which is defined as follows:…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, with advancements in pharmaceutical science, nano-crystallized megestrol acetate (NCMA) has been developed. Through animal and human studies, nano-crystallization has been found to enhance bioavailability in a fasting administration to some extent, thereby compensating for reduced systemic exposure compared with that in a fed administration [5][6][7][8].…”
mentioning
confidence: 99%
“…Based on the above results the authors stated that, with oral administration of nanocrystal formulation, systemic exposure to megestrol acetate is less affected by the lack of concomitant intake of food and the authors concluded that megestrol acetate's nanocrystal formulation could be more effective in treating patients with cachexia. 22…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Conventional treatment and some novel carrier system have the disadvantage of stability efficacy, bioavailability and toxicity; therefore, some of the drugs are formulated in the NCs l form and commercialized for effective treatment. Some of the Marketed NCs and their method of preparation are summarized in Table 2 [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108].…”
Section: Marketed Ncsmentioning
confidence: 99%